Public relations in Asia pacific : communicating effectively across cultures - Devereux, Mary M., ....-; Peirson-Smith, Anne, ....- (Singapore : John Wiley & Sons, 2009)
Public Relations in Asia Pacific reflects the growing professionalism in the practice of public relations in the world's fastest expanding economy. It is a carefully drawn road map, both strategically and tactically, for all manner of entities, for profit and not-for-profit on how to establish and maintain effective relationships with their numerous stakeholders. Particularly insightful are the many examples of public relations in action within the Asia Pacific region. It's a "must" read for those interested in public relations careers and those new to the profession; and it's a first-rate refresher for the established professional.
Keywords: Go international; International office; Public relations